2023
DOI: 10.3390/agronomy13051400
|View full text |Cite
|
Sign up to set email alerts
|

A Fertilization Decision Model for Maize, Rice, and Soybean Based on Machine Learning and Swarm Intelligent Search Algorithms

Abstract: Background: The application of base fertilizer is significant for reducing agricultural costs, non-point source pollution, and increasing crop production. However, the existing fertilization decision methods require many field observations and have high prices for popularization and application. Methods: This study proposes an innovative model integrating machine learning (ML) and swarm intelligence search algorithms to overcome the above issues. Based on historical data for maize, rice, and soybean crops, ML … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 56 publications
0
5
0
Order By: Relevance
“…Random forest and XGBoost thus showed "substantial" performance for maize yield prediction [69]. In previous studies, the accuracy of XGBoost to predict grain yield was found to be R 2 = 0.66-0.81 and RMSE = 0.92-1.68 Mg ha −1 [37,61,71]. In comparison, the accuracy (R 2 ) of decision-tree models applied to healthcare and genomics ranged from 80 to 88% [72,73].…”
Section: Model Accuracymentioning
confidence: 88%
See 1 more Smart Citation
“…Random forest and XGBoost thus showed "substantial" performance for maize yield prediction [69]. In previous studies, the accuracy of XGBoost to predict grain yield was found to be R 2 = 0.66-0.81 and RMSE = 0.92-1.68 Mg ha −1 [37,61,71]. In comparison, the accuracy (R 2 ) of decision-tree models applied to healthcare and genomics ranged from 80 to 88% [72,73].…”
Section: Model Accuracymentioning
confidence: 88%
“…The prediction accuracy of EONR is generally lower than grain yield prediction. Previous studies reported R 2 values of 0.36-0.86 and RMSE of 33-57 kg N ha −1 [18,37,71]. Indeed, the selected functions and their accuracies vary widely among sites [13] potentially injecting bias and errors [21].…”
Section: Model Accuracymentioning
confidence: 97%
“…These models incorporate complex parameters that are difficult to model, lack generalizability, and cannot be dynamically updated (Liu et al, 2019). Mathematical models generally take soil nutrient test results or remote sensing images as data sources and establish fertilizer effect equations based on statistical regression (Wang et al, 2020), machine learning (Gao et al, 2023), and deep learning (Escalante et al, 2019). They tend to be objective but offer poor interpretability and low reuse.…”
Section: Introductionmentioning
confidence: 99%
“…According to current projections, it is likely that the high prices of soybeans and corn will continue during the marketing period of the 2022/2023 crops [6]. Given this scenario, analyses, comparisons, and forecasts of production costs in agribusiness have been utilized as tools for decision-makers [7][8][9]. Pitrova et al (2020) [10] and Amorim et al (2020) [11] mentioned that computational simulation has proven to be an appropriate support tool for decision-making on rural properties.…”
Section: Introductionmentioning
confidence: 99%